Fort-NoCs: Mitigating the threat of a compromised NoC - Ancajas, Dean Michael; Chakraborty, Koushik; Roy, Sanghamitra (Proceedings - ACM IEEE Design Automation Conference, 2014)
In this paper, we uncover a novel and imminent threat to an emerging computing paradigm: MPSoCs built with 3rd party IP NoCs. We demonstrate that a compromised NoC (C-NoC) can enable a range of security attacks with an accomplice software component. To counteract these threats, we propose Fort-NoCs, a series of techniques that work together to provide protection from a C-NoC in an MPSoC. Fort-NoCs's foolproof protection disables covert backdoor activation, and reduces the chance of a successful side-channel attack by "clouding" the information obtained by an attacker. Compared to recently proposed techniques, Fort-NoCs offers a substantially better protection with lower overheads.